Mental health problems among economically disadvantaged adolescents in an increasingly unequal society: A Swedish study using repeated cross-sectional data from 1995 to 2011 - Yunhwan Kim; Curt Hagquist (Elsevier, 2018)
Increasing inequality in many societies highlights the importance of paying attention to differences in mental health between the economically disadvantaged adolescents and the non-disadvantaged adolescents. Also important is to understand how changing inequality in society over time influences adolescents' mental health at the population- and individual-level. The current study examined to what extent increased societal-level income inequality over time, individual-level experiences of economic disadvantage and the cross-level interaction between the two explained Swedish adolescents' mental health problems from 1995 to 2011. We used repeated cross-sectional data collected 6 times between 1995 and 2011 in Sweden. Each time, approximately 2500 students in grade 9 completed a questionnaire during the spring semester. The adolescents provided self-report data on the frequency of their experiences of unaffordability of daily leisure activities (concert, movie, sports, and dance). They also reported their psychosomatic symptoms, which was used as a measure of mental health problems. We used the household equalised disposable income Gini coefficient as an indicator of societal income inequality. A real gross domestic product (GDP) per capita was controlled for in order to rule out potential effects of economic growth in the society over time. Multilevel regression analyses were conducted in which students were nested in years of investigations. Adolescents who experienced unaffordability of daily leisure activities reported more mental health problems. Societal income inequality was not directly associated with the adolescents' mental health. However, among girls the effects of experiences of unaffordability on mental health were stronger for all but one (sports) activities, and among boys for one activity (sports) when societal-level inequality was greater. Individual-level economic disadvantage are detrimental for adolescents' mental health, both directly and interactively with societal-level economic inequality. Some suggestions for practice and future studies are made for mental health among adolescents in societies where increasing inequality is observed. Keywords: Mental health problems, Inequality, Unaffordability, Economic disadvantage